DEVELOPMENT OF BRAILLE AUDIOBOOK AS A LEARNING TOOL AT YPAB SURABAYA SPECIAL ELEMENTARY SCHOOL - Shofa Aulia Aldhama; Gunawan Setia Prihandana; M. Aufa Ghozi Adli Leksono; Venni Tanujaya; Anindita Nur Sabrina; Muthiatun Nafiah; Nurul Mufidah; Asseghaf Bintang Ramadhani; Mikhael Dananda Agusta; Hangger Nandhityo (Universitas Airlangga, 2026)
Educational approaches for students with visual impairments continue to evolve, emphasizing the importance of assistive learning media to support independent learning. This community service activity focuses on the development and testing of a learning aid called the Braille Audio Book, which integrates tactile Braille characters with audio feedback to assist blind students in learning Braille more independently. This activity was conducted at SLB A YPAB Surabaya, involving 15 visually impaired students from grades 2 to 5. The implementation of the activity included product demonstrations, device usability testing, and the evaluation of students' abilities through Braille character recognition tests before and after the intervention (pre-test and post-test). Quantitative evaluation results showed an increase in student enthusiasm, reaching 85% in the excellent category when using the device. However, for students with more advanced skills, the development of more varied content is required. In addition, several technical issues related to the device casing design were identified, indicating the need for further refinement to improve usability and durability. Overall, the Braille Audio Book demonstrates promising potential as an assistive learning medium to support Braille literacy among visually impaired students.